PEMANFAATAN LIMBAH PETERNAKAN DALAM KONSEP PERTANIAN TERPADU GUNA MEWUJUDKAN PERTANIAN YANG BERKELANJUTAN - Suryono Suryono; Widyatmani Sih Dewi; Sumarno Sumarno (Universitas Sebelas Maret, 2014)
Utilization of farm wastes in order to realize the concept of integrated farming is a sustainable agriculture community service program in cooperation with two partners, namely : ( 1 ) quail - catfish Breeders 'Agribird', and ( 2 ) dairy farms and agricultural businesses